2007
DOI: 10.1111/j.1529-8817.2007.00393.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the life cycles of Alexandrium tamutum and Alexandrium minutum (Gonyaulacales, Dinophyceae) in culture1

Abstract: The microalgal genus Alexandrium includes species known to produce paralytic shellfish poisoning (PSP). Due to the importance of discriminating between HAB-forming species, we compared the undescribed life-cycle pattern of Alexandrium tamutum Montresor, Beran et U. John and of its toxic relative Alexandrium minutum Halim. Sexual stages, asexual and sexual division, mating type, and nuclear morphology were studied in both species. Sexual cysts are known to be morphologically identical. However, the relative siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
112
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(118 citation statements)
references
References 46 publications
(103 reference statements)
6
112
0
Order By: Relevance
“…These estimates were based on a comparison with the DNA content of the dinoflagellate species Alexandrium minutum, whose DNA content was previously shown to be almost identical to that of our K. foliaceum strain (Figueroa et al 2007). Our results were obtained by a different methodology than Kite et al (1988), which may explain why these authors reported higher DNA content values for K. foliaceum than determined in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These estimates were based on a comparison with the DNA content of the dinoflagellate species Alexandrium minutum, whose DNA content was previously shown to be almost identical to that of our K. foliaceum strain (Figueroa et al 2007). Our results were obtained by a different methodology than Kite et al (1988), which may explain why these authors reported higher DNA content values for K. foliaceum than determined in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Study of the dinoflagellate and endosymbiont cell cycle by flow cytometry: DNA analyses were done following the method described by Figueroa et al (2006Figueroa et al ( , 2007. Culture aliquots of 45 ml were fixed in 1% paraformaldehyde for 10 min at room temperature and washed with PBS Life History of Kryptoperidinium foliaceum (Sigma-Aldrich, USA, #P4417), pH 7.…”
Section: Methodsmentioning
confidence: 99%
“…The fusion of compatible gametes from the same clone (selfing, homothallism) results in a lack of effective recombination, whereas the fusion of gametes from different clones (outcrossing, heterothallism) may result in recombination. Therefore, A. catenella from Thau Lagoon may ex- (13), and Alexandrium peruvianum (12), whose sexual stages have been well described. Such knowledge is essential for understanding the origin and occurrence of toxic events due to A. catenella.…”
Section: Discussionmentioning
confidence: 99%
“…The initial IFCB analysis of this sample Other flow cytometry studies of dinoflagellate sexual conjugation have not detected premeiotic replication (Parrow, Burkholder et al 2002;Parrow and Burkholder 2003;Figueroa, Garces et al 2007;Figueroa, Garcés et al 2010) and some have suggested that dinoflagellates may undergo a unique meiosis that does not require premeiotic replication (Beam and Himes 1980;Kita, Fukuyo et al 1993;Elbrachter 2003;Parrow and Burkholder 2003). The notion that dinoflagellate could carry out a unique dinoflagellate meiosis stems from pioneering genetic studies of the saprobic dinoflagellate, Crypthecodinium cohnii, which showed that these cells only rarely yield tetratype sexual progeny (Beam, Himes et al 1977;Beam and Himes 1980), and also by a lack of reports of chiasmata between dinoflagellate chromosomes.…”
Section: Assessment Of Dna Content Measurementsmentioning
confidence: 99%